Pembebasan Sanksi Pajak Dan Kesadaran Pembayaran Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor - Istianah, Istianah; Rohma, Frida Fanani (Universitas Katolik Soegijapranata, Semarang, 2025)
The aim of this research is to find out whether exemption from tax sansction and awareness of tax payments affect motor vehicle taxpayer compliance in the Bangkalan Samsat using descriptive qualitative methods whit secondary data obtained directly from the Bangkalan Samsat. The resultof the research show that there is a negative influence of exemption from tax sanctions and awareness of tax payments on mandatory motor vehicle compliance. Suggestions for future reseaechers could be touse a questionnaire to better understand the responses of each taxpayer who made payments and also those who did not make payments.